Strong Unique Continuation for Solutions of a p(x)-Laplacian Problem - Johnny Cuadro; Gabriel López (International Journal of Mathematics and Mathematical Sciences)
We study the strong unique continuation property for solutions to the quasilinear elliptic equation -div(|∇u|p(x)-2∇u)+V(x)|u|p(x)-2u=0  in  Ω where V(x)∈LN/p(x)(Ω), Ω is a smooth bounded domain in ℝN, and 1<p(x)<N for x in Ω.